KOMPETENSI GURU DALAM PENGGUNAAN TEKNLOGI INFORMATIKA (TIK) PADA KEGIATAN PEMBELAJARAN PAI DI SDN PASIR BATANG 01 MANONJAYA TASIKMALAYA - Putra, Naufal Kusuma; Suhendra; Salati Asmahasanah (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study aims to describe the competence of teachers in the use of Information and Communication Technology (ICT) in Islamic Religious Education (PAI) learning activities at SDN Pasir Batang 01 Manonjaya, Tasikmalaya. Along with the development of the times and technological advancements, teachers' ability to integrate ICT into the learning process is an important need to increase the effectiveness and attractiveness of learning, especially in PAI subjects. The method used in this study is qualitative descriptive with data collection techniques through observation, interviews, and documentation. The results of the study showed that some teachers already have basic competencies in using ICT such as the use of presentation media, learning videos, and other supporting applications. However, the use of ICT is still limited due to infrastructure constraints and lack of continuous training. Therefore, efforts are needed to improve teacher competence through.